Study of climatic factors on the population dynamics of Pyricularia oryzae on some varieties of paddy rice (Oryza sativa) - SOPIALENA SOPIALENA; PRATIWI JATI PALUPI (Society for Indonesian Biodiversity, 2017)
Sopialena, Palupi PJ. 2017. Study of climatic factors on the population dynamics of Pyricularia oryzae on some varieties of paddy rice (Oryza sativa). Biodiversitas 18: 701-708. The occurrence of plant diseases is influenced by three factors: pathogen, environment, and host. Environment playing important role in the development of the disease is the climatic factor, whereas the resistance of plants also influences the development of disease. The research was conducted during five months from April to August 2016 and the location of the research was in paddy fields in Tanah Merah, North Samarinda, East Kalimantan, Indonesia. The study aims to determine the climatic factors (temperature and humidity) which are most dominant to the rate of spot width, the infection rate of pathogen attack intensity on Pyricularia oryzae and the development of P. oryzae spores in several varieties of paddy rice (Inpari 7, Ciherang and Cibogo). The parameters in the study are climate factors namely humidity and temperature, the width rate of spot blast disease, the attack intensity of pathogenic P. oryzae and the spores number of P. oryzae. Research shows that the population of P. oryzae is strongly influenced by temperature. Low temperature is the most dominant factor affecting the rate of infection of blast disease. The number of pathogen population also affects the attack intensity of the disease. A higher population of P. oryzae led to higher intensity of blast disease in rice plants. Moreover, varieties of rice plants also affect P. oryzae attack. The more vulnerable the plants, the higher level of P. oryzae attack on the plant. The lowest intensity attack of the disease is found in Ciherang, then Cibogo and the most vulnerable is Inpari 7.